Camera constant in the case of two media photogrammetry - Agrafiotis, Panagiotis; Georgopoulos, Andreas (My University, 2015)
Refraction is the main cause of geometric distortions in the case of two media photogrammetry. However, this effect cannot be compensated and corrected by a suitable camera calibration procedure (Georgopoulos and Agrafiotis, 2012). In addition, according to the literature (Lavest et al. 2000), when the camera is underwater, the effective focal length is approximately equal to that in the air multiplied by the refractive index of water. This ratio depends on the composition of the water (salinity, temperature, etc.) and usually ranges from 1.10 to 1.34. It seems, that in two media photogrammetry, the 1.33 factor used for clean water in underwater cases does not apply and the most probable relation of the effective camera constant to the one in air is depending of the percentages of air and water within the total camera-to-object distance. This paper examines this relation in detail, verifies it and develops it through the application of calibration methods using different test fields. In addition the current methodologies for underwater and two-media calibration are mentioned and the problem of two-media calibration is described and analysed.
Keywords: Calibration; Camera constant; Refraction; Two media photogrammetry